A cost analysis of robotic vs. video-assisted thoracic surgery: The impact of the learning curve and the COVID-19 pandemic - Harrison, Oliver J.; Maraschi, Alessandro; Routledge, Tom; Lampridis, Savvas; LeReun, Corinne; Bille, Andrea (Frontiers in Surgery, 2023)
Introduction Robot-assisted thoracoscopic surgery (RATS) is an alternative to video-assessed thoracoscopic surgery (VATS) for the treatment of lung cancer but concern exists regarding the high associated costs. The COVID-19 pandemic added further financial pressure to healthcare systems. This study investigated the impact of the learning curve on the cost-effectiveness of RATS lung resection and the financial impact of the COVID-19 pandemic on a RATS program. Methods Patients undergoing RATS lung resection between January 2017 and December 2020 were prospectively followed. A matched cohort of VATS cases were analyzed in parallel. The first 100 and most recent 100 RATS cases performed at our institution were compared to assess the learning curve. Cases performed before and after March 2020 were compared to assess the impact of the COVID-19 pandemic. A comprehensive cost analysis of multiple theatre and postoperative data points was performed using Stata statistics package (v14.2). Results 365 RATS cases were included. Median cost per procedure was £7,167 and theatre cost accounted for 70%. Major contributing factors to overall cost were operative time and postoperative length of stay. Cost per case was £640 less after passing the learning curve (p<0.001) largely due to reduced operative time. Comparison of a post-learning curve RATS subgroup matched to 101 VATS cases revealed no significant difference in theatre costs between the two techniques. Overall cost of RATS lung resections performed before and during the COVID-19 pandemic were not significantly different. However, theatre costs were significantly cheaper (£620/case; p<0.001) and postoperative costs were significantly more expensive (£1,221/case; p=0.018) during the pandemic. Discussion Passing the learning curve is associated with a significant reduction in the theatre costs associated with RATS lung resection and is comparable with the cost of VATS. This study may underestimate the true cost benefit of passing the learning curve due to the effect of the COVID-19 pandemic on theatre costs. The COVID-19 pandemic made RATS lung resection more expensive due to prolonged hospital stay and increased readmission rate. The present study offers some evidence that the initial increased costs associated with RATS lung resection may be gradually offset as a program progresses.